Red seaweeds Porphyra umbilicalis and Grateloupia turuturu display antigenotoxic and longevity-promoting potential in Drosophila melanogaster. Issue 4 (2nd October 2019) - Ferreira, João; Marques, Ana; Abreu, Helena; Pereira, Rui; Rego, Andreia; Pacheco, Mário; Gaivão, Isabel
ABSTRACT: The red seaweeds Porphyra umbilicalis and Grateloupia turuturu are often used for human consumption. Nevertheless, there are knowledge gaps in studies focusing on their potential for genoprotection and in vivo studies assessing effects of whole algae intake. Thus, P. umbilicalis and G. turuturu were evaluated as genome integrity- and longevity-promoters, using a somatic mutation and recombination test (SMART) and longevity assay, respectively, in Drosophila melanogaster . For the longevity assay, alga supplementation (1.25, 2.5, 5, 10 and 20% (w/w)) occurred until eclosion (emergence as adults). Flies were counted once a week until death. For SMART, the diet was supplemented with 5 and 10% P. umbilicalis and 10 and 20% G. turuturu until adults' eye observation. Streptonigrin (SN) was added as genotoxic insult. Supplementations with 10% P. umbilicalis and 20% G. turuturu promoted longevity increases, with G. turuturu achieving the highest potential. Basal DNA damage (without SN-challenge) was reduced in flies supplemented with 10% P. umbilicalis and 10 and 20% G. turuturu . All seaweed concentrations demonstrated antigenotoxic potential against SN-induced genotoxicity. At the 10% supplementation level, a higher antigenotoxicity was displayed by G. turuturu . Overall, the best promoter of genome integrity was 20% G. turuturu . The seaweeds proved to be promoters of a safe and healthy nutrition as functional foods.